Characteristics analysis of interior and inset type permanent magnet motors for electric vehicle applications - Pudji Irasari; Ketut Wirtayasa; Puji Widiyanto; Muhammad Fathul Hikmawan; Muhammad Kasim (National Research and Innovation Agency, 2021)
Permanent magnet motors (PMMs) are widely used in electric vehicles because of their benefits. Based on the permanent magnet topologies on the rotor, PMMs are classified into three types: surface mounted PMM, inset PMM, and interior PMM. This paper discusses a comparison of the characteristics of interior and inset types of PMMs for electric vehicle applications. The study aims to find out the effect of the rotor construction on the magnetic characteristics, torque-speed characteristics, and cogging torque. Simulations were carried out analytically and numerically using the FEMM 4.2 software. The simulation results at the base speed show that the interior PMM generates a higher torque but with a lower rotation, namely 56.47 Nm and 3162 rpm, respectively, while the inset PMM produces higher rotation 4200 rpm but lower output torque of 46.01 Nm. However, with a higher saliency ratio, the interior PMM produces higher maximum torque and speed at both constant torque and field weakening regions than the PMM inset, which is 92.87 Nm and 6310 rpm, consecutively. In terms of cogging torque, the interior PMM raises it slightly higher (2.90 Nm) than the inset PMM (1.93 Nm). The results conclude that, in general, the interior PMM shows better performance in all studied regions and is preferable for electric vehicle applications.